2013
DOI: 10.3389/fpls.2013.00410
|View full text |Cite
|
Sign up to set email alerts
|

Sodium transport system in plant cells

Abstract: Since sodium, Na, is a non-essential element for the plant growth, the molecular mechanism of Na+ transport system in plants has remained elusive for the last two decades. The accumulation of Na+ in soil through irrigation for sustainable agricultural crop production, particularly in arid land, and by changes in environmental and climate conditions leads to the buildup of toxic level of salts in the soil. Since the latter half of the twentieth century, extensive molecular research has identified several classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 90 publications
4
100
0
Order By: Relevance
“…2A and 2B). Consistently, a low Na + accumulation together with elevated K + /Na + ratio has been considered as an important mechanism for salt tolerance in plant species (Yamaguchi et al, 2013;Miranda et al, 2017). In fact, our findings demonstrated that the most salt tolerant sorghum plants (P10-acclimated) showed a lower content of toxic Na + ions coupled to greater K + /Na + ratio in leaves ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…2A and 2B). Consistently, a low Na + accumulation together with elevated K + /Na + ratio has been considered as an important mechanism for salt tolerance in plant species (Yamaguchi et al, 2013;Miranda et al, 2017). In fact, our findings demonstrated that the most salt tolerant sorghum plants (P10-acclimated) showed a lower content of toxic Na + ions coupled to greater K + /Na + ratio in leaves ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…TaSOS1 gene has been reported to be associated with sodium exclusion at plasmalemma level in root tissues (Apse and Blumwald 2002). Other reports also indicated higher expression of TaSOS1 gene transcript in roots (Benderradji et al 2011;Cuin et al 2011;Yamaguchi et al 2013) under salt stress. There was 27.57-fold increase in the expression of TaNHX1 gene in leaf and 3.07-fold in the roots Kh 65 while 3.67-fold in leaf and 0.87-fold in root of HD 2009 under salt stress.…”
Section: Na + Concentration and Expression Analysis Of Tasos1 And Tanhx1mentioning
confidence: 77%
“…Osmotic stress causes inhibitions of water uptake, cell elongation, and leaf development, while ionic stress results in high Na accumulation in the shoots, which decreases protein synthesis, enzymatic reactions, and photosynthetic processes (Zhu, 2001;Horie et al, 2012;Deinlein et al, 2014). Therefore, restricting Na accumulation to the shoots (especially in the leaves) is important to protect plants from ionic Na + stress (Davenport et al, 2005;Yamaguchi et al, 2013).…”
mentioning
confidence: 99%